Capacity of Japanese institutions to manage obstetrical disseminated intravascular coagulation in 2018: A national surveillance questionnaire and retrospective cohort study. Issue 9 (12th July 2021) - Morikawa, Mamoru; Nii, Masafumi; Nakabayashi, Yasushi; Itakura, Atsuo; Kobayashi, Takao; Adachi, Tomoko
Abstract: Aim: To investigate the management of obstetrical disseminated intravascular coagulation (DIC) in Japan. Methods: We sent a surveillance questionnaire to 2299 institutions to collect details about the deliveries they performed in 2018. We investigated differences in the management of obstetrical DIC among three types of institutions: perinatal medical centers (PMCs), general hospitals with obstetrical facilities (GHs), and maternal clinics with beds (MCs). Results: We received responses from 703 institutions (30.6% of the total mailed) with results of 306 799 women who gave birth in 2018. In Japan, the potential to treat postpartum hemorrhage and obstetrical DIC was high in the PMC group, moderate in the GH group, and low in the MC group. The incidence of obstetrical DIC in the PMC group (0.44%) was significantly higher than that in the GH (0.21%) and MC (0.06%) groups. The mortality of women with obstetrical DIC in PMCs (1.3%) was similar to that in GHs (0.6%) and MCs (0.0%). The percentages of PMCs that always or sometimes transfused fresh frozen plasma or fibrinogen concentrates (100% and 42.2%, respectively) were significantly higher than those in the GH (88.2% and 29.5%, respectively) and MC groups (29.4% and 5.3%, respectively). Furthermore, institutions whose internal protocols mandated that replacement therapy be always administered in women with obstetrical DIC scores of ≥8 had similar protocols to those for women with fibrinogen levels of ≤1.5 g/L. Conclusions: The capacity to provide therapy for postpartum hemorrhage and obstetrical DIC varied widely among the three groups of institutions.